ANALISIS PELANGGARAN HARAPAN NONVERBAL DALAM JARAK PERSONAL KARYAWAN RIAU POS PEKANBARU - ", M.Syukri; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Violations within personal nonverbal expectations assume that everyone has certain expectations on nonverbal behavior of others and the need to communicate personal distance. If these expectations are violated, people will react to give a positive or negative ratings to reflect the characteristics of the offender. The authors study aimed to determine describe and analyze the nonverbal expectancy violations within personal employee Riau Pos Pekanbaru and also to determine whether the reward valence communicator affect employee assessment toward nonverbal expectancy violations within personal in Riau Pos Pekanbaru.This study used a qualitative method with descriptive analysis approach. Subjects were all employees in Riau Pos Pekanbaru with a total of as many as 81 (eighty one) of the specified categories based on purposive sampling. The collection of data obtained through observation and interviews.The results showed that employees Riau Pos Pekanbaru takes time and personal space for solitude could not be bothered. Time and distance required to be alone addressed and included in the positive offense because of the time and personal space that is required is to seek ideas on the news. Violations expectations in Riau Pos Pekanbaru makes employees work to be uncomfortable eg employees communicate with high intonation, but for employees Riau Pos it has become a habit, let alone still around work. They do not feel disadvantaged as long as it can help clinch a job, help, correct, then it is considered reasonable. So violations are not addressed expectations negative, but positive. When violations occur, the negative expectations of nonverbal communication is not continued and neglected.Keyword: In violation of hope nonverbal distance of employee personal riau pos pekanbaru